(untitled) (Indian Journal of Arid Horticulture, 2025)
The salinity and alkalinity indices for cultivated soils of Bikaner district were 1.06, 2.96 and 1.04, 3.00 for surface and subsurface soils, respectively. The fertility index for organic carbon, available nitrogen, phosphorus and potassium were 1.00, 1.09,1.51 and 2.01 for surface and 1.00, 1.04,1.50 and 1.96 for subsurface soils. Soils have slight salinity and moderate alkalinity problem and found to be low in organic carbon and available nitrogen, low to medium in available phosphorus and medium in available potassium.